Factors limiting the implementation of mechanical harvesting of sugarcane in Campos dos Goytacazes, RJ, Brazil - Solano, Cristobal Soto; Ponciano, Niraldo José; de Azevedo, Hamilton Jorge; de Souza, Paulo Marcelo (Revista Ceres, 2017)
The objective of this research was to identify and characterize the main technical factors that affect the deployment of the mechanized harvesting of sugarcane in Campos dos Goytacazes, Rio de Janeiro, Brazil. In general, it can be stated there were restrictive factors related to machinery, administrative management, and technical planning. We identified significant technical restrictions in the planting system, particularly in relation to the size and shape of the plots, length of the rows, row spacing, and inadequate varieties. For efficient use of mechanized harvesting, a technical planning is necessary with changes in the cropping system, adopting wider and more uniform plots regarding to its format, with rows over 500 m length and row spacing of 1.50 m and upright, productive, and deep-rooted varieties.